Genetic aspects of hereditary motor and sensory neuropathy (types I and II). Issue 5 (October 1980) - Harding, A E; Thomas, P K
Abstract : The genetic features of a series of 227 patients with hereditary motor and sensory neuropathy (HMSN) have been analysed. The series comprised 119 index cases from 110 families in which 108 affected relatives were identified. The cases were classified as having type I or type II HMSN on the basis of nerve conduction studies. Inheritance in the type I cases was autosomal dominant in 139 (45 families) and autosomal recessive in eight (four families) with 26 single cases. For the type II cases, 35 (17 families) were autosomal dominant and three (two families) autosomal recessive with 16 single cases. A significant excess of males was present in the combined single and recessive type I cases and in the type I index cases. No X linked pedigrees were identified. The correlation coefficients for motor nerve conduction velocity between the index cases and their relatives suggested further genetic heterogeneity in the type I cases. Parent-offspring and sib-sib correlation coefficients for age of onset in the dominantly inherited type I cases were less than 0·5. There was therefore no strong suggestion of genetic heterogeneity in terms of age of onset. The severity of muscle weakness did not differ between the dominantly inherited type I and type II cases. In both types males had higher weakness scores than females, but there was no difference for either type in relation to the sex of the affected parent. Segration analysis suggested that approximately 70% of the single generation type I cases were of autosomal recessive inheritance, whereas only about 25% of the single generation type II cases were recessive. Biological fitness was reduced in type II HMSN, which would support a higher proportion of new dominant mutations among the single cases of this type than in type I. Despite the excess of males in the type I single case/recessive category, a contribution of cases with X linked recessive inheritance is improbable. Single cases of HMSN, especially the type II form in view of its later onset, are likely to be unrecognised clinically and will be classified as `cryptogenic' neuropathy. As in many affected subjects the degree of disability is minimal, a careful scrutiny of the relatives is merited in such instances.